Proposed Speedy Moisture Test Calibration Chart on Indonesian Road Embankments - Soebagio Soebagio; Danang Setiya Raharja; Utari Khatulistiani (Kadiri University, 2023)
Embankment construction is generally carried out using borrow materials. The water content of embankment material significantly affects the compaction quality. Measuring water content in the field typically uses a speedy moisture test (SMT) because the process is simple, and the result is obtained immediately. The accuracy level of the SMT is relatively high. However, it still needs to be corrected using a calibration chart for a more precise measurement. This research aims to determine the accuracy of the SMT tool compared to the standard oven-dry method, especially on borrow materials in East Java. The experimental method was used with soil samples from Pasuruan and Mojokerto borrow. Standard index properties tests and soil compaction tests were conducted to determine soil type and obtain optimum water content. The water content varies in several levels and is measured using SMT and oven-dry methods. The regression was performed to make a correlation, while RMSE and simple paired T-test were conducted to investigate the accuracy level of the correlation chart from this research, respectively. It was found that the soil samples used met the requirements as embankment soil (SW and SM). The proposed calibration chart is presented with the SMT-corrected water content equation (WSMT-corrected = 0.9815WSMT – 1.4323 ). This equation has a coefficient of determination (R2) equal to 0.95, which mean a very strong relationship. The proposed calibration chart performs well according to RMSE, which is equal to 2.41 and paired T-test result. This proposed calibration chart can be widely used in road embankment practice in Indonesia.